Outmigration and labor mobility issues and policies in Nepal - Kharel, A.; Sugden, F.; Gupta, S. (University of London, 2023)
Nepal’s labor migration history dates back to the colonial period in India when Nepali youths were recruited in the army of the East India Company in the early 19th century, and even prior to this period, Nepali men served in the army of Shikh ruler Ranjit Singh in Punjab (included territories of present-day India and Pakistan). This was followed by seasonal and longer-term labor migration to India. In the last 30 years, migration has reached exceptionally high levels, with the new generation of labor migrants heading to the Gulf States and Malaysia, as well as other destinations such as South Korea, Japan, Poland and Romania. The 1981 Nepali census classified over 400,000 household members as ‘absentees’ (those who were away or intend to be away from home for six or more months) and this increased to about 2.2 million by 2021. The destination of migrants over these years changed considerably. While in 1980, an overwhelming majority (93%) went to India, from the 1990s onwards, this shifted to the Arabian Gulf States and Malaysia, which accounted for over 90% of migrants by the 2010s, with fewer than 10% continuing to travel to India.